Township Tourism: The politics and socio-economic dynamics of tourism in the South African township: Umlazi, Durban - Chili, Nsizwazikhona Simon (Journal of Economics and Behavioral Studies, 2015)
The paper analyses how tourism development at Umlazi which is one of the second biggest Townships in the Southern hemisphere has been hampered by politics and socio economic dynamics that stifle the empowerment of both tourism entrepreneurs and local communities respectively. The impacts of tourism have been given much attention by scholars to examine the perceptions and attitudes of local residents towards Township tourism in South Africa. However, there is little research that focuses on how much political and economic dynamics of the past and present dispensations have adversely impacted on the tourism economic development of small emerging entrepreneurs and local residents of the Townships. This study attempts to make a little contribution to South African Township tourism by examining political and economic dimensions that hinder small businesses and local residents of uMlazi to thrive and get empowered through tourism. Township tourism in South Africa has slightly improved and grown in popularity since 1994 and is considered by the government and other social agents to be an appropriate opportunity for small businesses and the stimulation of local economic development. However, the paper argues that tourism fails to act as a panacea of economic development in the township of Umlazi, since there is lack of business opportunities, intervention and support of local government, private sector and racial groups that are endowed with more than enough financial resources. Data were collected by means of interviews that allowed the interviewer to pose some open-ended questions so that the interviewee could express his or her own opinion freely for the extraction of more information. Based on 30 respondents surveyed, the findings show that there are numerous obstacles that are directly linked to political and economic dynamics. These obstacles include lack of political intervention and financial support for tourism entrepreneurs and local residents of UMlazi Township. On the whole respondents viewed Township tourism negatively. They were generally of the idea that township tourism can only be of benefit to residents once it is often visited by racial groups who are better off financially after their fears about safety and security have been allayed.